STRATEGI BISNIS KOPICENTRUM DI DRAMAGA BOGOR - Sari, Widia Melini Indah; Suharno; Etriya, Etriya (Forum Agribisnis, 2025)
A survey conducted in 2024 showed that coffee consumption reached more than 300 thousand tons with the majority of consumers coming from the younger generation. One of those who took advantage of these opportunities and chances was Kopicentrum in Dramaga Bogor. However, until now the absence of a comprehensive strategic guide has become one of the obstacles in winning market competition. This study aims to overcome the chalenges that occur by identifying internal and external factors and exploring alternative business strategies through IE matrix analysis. This research is a case study research at Kopicentrum Dramaga Bogor with data collection through interviews, observations, and questionnaires to management, employees, and customers, which are analyzed using the IFE, EFE, and IE Matrices. The results of the study indicate that Kopicentrum has high internal strength (IFE score 3.68) and moderate external responsiveness (EFE score 2.90), pacing it in Quadrant IV in the IE Matrix with the right strategy in the form of Grow and Build, including maintaining market position, product enhancement, internal efficiency, and strategic alliances with local farmers. This study has implications for the importance of flexibe and context-based strategies, art, and needs to be adjusted to the unique conditions of each business to maintain competitiveness in a dynamic market.